Two new combinations of Medaurini (Phasmatodea: Phasmatidae: Clitumninae) from Yunnan Province, China - Xie, Chong-Xin; Wen, Jun; Wang, Chen; Wang, Zhao-Zi; Qian, Yu-Han (Zootaxa, 2023)
Two new combinations are proposed for Chinese species previously described in the endemic Australian genus Pachymorpha Gray, 1835: Interphasma belocerca (Chen & He, 2008) comb. nov., of which the male and egg are described are illustrated for the first time and Neomedaura arguta (Chen & He, 2008) comb. nov., the first report of the genus Neomedaura Ho, 2020, in China.